Everyday and major experiences of racial/ethnic discrimination and sleep health in a multiethnic population of U.S. women: Findings from the Sister Study - Gaston, Symielle A. (Sleep Med, 2020)
BACKGROUND: Perceived racial/ethnic discrimination and poor sleep occur across all races/ethnicities in the U.S., though both are most common among racial/ethnic minorities. Few studies have investigated associations between perceived racial/ethnic discrimination and various sleep dimensions in a multiethnic population. METHODS: We analyzed cross-sectional associations among 40,038 eligible Sister Study participants (enrollment: 2003–2009) who reported ever/never experiencing specific types of everyday (e.g., treated unfairly at a store or restaurant) or major (e.g., unfairly stopped, threatened, or searched by police) discrimination attributed to their race/ethnicity during a follow-up survey in 2008–2012. Participants also reported short sleep duration (<7 hours), sleep debt (≥2-hour difference between longest and shortest sleep duration), frequent napping (≥3 times/week), and insomnia. Poisson regression with robust variance estimation, adjusted for sociodemographic and health characteristics, estimated prevalence ratios (PRs) and 95% confidence intervals (CIs) for the association between each type of racial/ethnic discrimination and each sleep dimension, overall and by race/ethnicity. RESULTS: Mean age was 55 ± 8.9 years, 89% were NH-white, 8% NH-black, and 3% Hispanic/Latina. NH-black participants were the most likely to report everyday (76% vs. 4% [NH-whites] and 36% [Hispanics/Latinas]) and major racial/ethnic discrimination (52% vs. 2% [NH-whites] and 18% [Hispanics/Latinas]). Participants who experienced both types versus neither were more likely to report short sleep duration (PR=1.17 [95% CI: 1.09–1.25]) and insomnia symptoms (PR=1.10 [1.01–1.20]) but not other poor sleep dimensions. CONCLUSIONS: Racial/ethnic minority women were most likely to experience racial/ethnic discrimination, which was associated with certain poor sleep dimensions among women of all races/ethnicities.